PENGARUH ARAH SUMBER CAHAYA MATAHARI TERHADAP PERTUMBUHAN SEMAI MERANTI MERAH (ShorealeprosulaMiq.) DI BAWAH NAUNGAN TEGAKAN KELAPA SAWIT - Marliana, Dian; Mardhiansyah, M.; Yoza, Defri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
Shorea spp. is one of the most widely used wood types by the community. In addition to the economic value of wood, the Shorea group also has a non-timber economic value. Plants need sunlight for growth and development. The intensity of light is one of the most important factors in the process of photosynthesis to produce energy as fuel for plant growth. Shade can be interpreted as a shelter or something that can protect plants from excessive direct sunlight. Shorea leprosula Miq. is a type of semi-tolerant plant that needs shade. In this study, we will try to apply the science of Agroforestry, which is a combination of plantation and forestry plants, by planting red meranti seedlings under the auspices of oil palm stands by paying attention to the direction of the source of sunlight. The method used in this study is a randomized block design (RCBD), which consists of 5 treatments and 4 groups. This study uses 5 treatments with different light source directions, namely A0 (Shade without Shade or control), A1 (Position of seedlings in the East), A2 (Position of seedlings in the North), A3 (Position of seedlings in the South) and A4 (Position of seedlings in the West). The direction of the light sourceÂ the position of seedlings in the south under the auspices of oil palm stands turn out to be better for plant growth because it gets a long period of light exposure from morning to evening.Â Keywords : source direction,sunlight,growth, Shorea leprosula Miq., shade, oil palm stand.